1987
DOI: 10.1016/0167-8760(87)90008-0
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials and item recognition in depressed, schizophrenic and alcoholic patients

Abstract: Auditory event-related potentials (ERPs) to pure tones and performance on a measure of item recognition were compared in 20 controls, 14 alcoholics, 20 depressed and 21 schizophrenic patients. Compared with normal controls, P2 and N2 were delayed and of diminished amplitude in the psychopathological groups. Increased amplitude of P1 in alcoholics, diminished N1 in depressed patients, increased latencies of N1 in schizophrenics and N2 in alcoholics were pathology-specific. Unusual patterns of response in the it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Amplitude and latency alterations have also been reported for the N1 (Ford et al 1994b;Kessler and Steinberg 1989;O'Donnell et al 1994), the P2 Sandman et al 1987), the N2 (Ford et al 1994b;Javitt et al 1995;O'Donnell et al 1993O'Donnell et al , 1994Sandman et al 1987), and, in the target minus standard difference wave, the mismatch negativity (Javitt et al 1995) and the N2 difference (N2d) . These components are thought to arise from a combination of neural sources in primary and secondary auditory cortical areas in the superior and lateral temporal lobes, with contributions from frontal lobe activity (Giard et al 1988(Giard et al , 1994Hegerl et al 1994;Pantev et al 1995;Ponton et al 1993;Rogers et al 1991;Tarkka et al 1995).…”
mentioning
confidence: 98%
“…Amplitude and latency alterations have also been reported for the N1 (Ford et al 1994b;Kessler and Steinberg 1989;O'Donnell et al 1994), the P2 Sandman et al 1987), the N2 (Ford et al 1994b;Javitt et al 1995;O'Donnell et al 1993O'Donnell et al , 1994Sandman et al 1987), and, in the target minus standard difference wave, the mismatch negativity (Javitt et al 1995) and the N2 difference (N2d) . These components are thought to arise from a combination of neural sources in primary and secondary auditory cortical areas in the superior and lateral temporal lobes, with contributions from frontal lobe activity (Giard et al 1988(Giard et al , 1994Hegerl et al 1994;Pantev et al 1995;Ponton et al 1993;Rogers et al 1991;Tarkka et al 1995).…”
mentioning
confidence: 98%
“…Patterson et al (1987) found that NI00 amplitude was smaller for alcoholics. Sandman et al (1987) found that the N1 and P2 components were smaller in alcoholic subjects.…”
Section: Introductionmentioning
confidence: 98%
“…Only one other study, however, has been found that attempted to predict alcoholic group membership by means of ERPs (Sandman et al, 1987).…”
Section: Discriminant Analysismentioning
confidence: 99%
See 2 more Smart Citations